Correlation Between Reading Fondness and Attitude Toward Science at Middle School - Tanti, Tanti; Kurniawan, Dwi Agus; Firmansyah, Riko; Zain, Muhammad Sofyan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This research was conducted to analyze the correlation between reading fondness and attitude toward science. The number of research samples was 145 students. The research method used is a mix of quantitative and qualitative instruments that are descriptive. Quantitative instrument data collection techniques in the form of questionnaires and observations, qualitative instruments in the form of documentation and interviews. The statistical results of the attitude toward science variable, the average student chooses neutral in all indicators. The reading fondness variable of indicators general attitude towards reading and students' reading preferences average students chose neutral, the effect of reading on the ability of students chose to agree, and negative views of students towards reading chose not to agree. Based on the significance of 0.048 <0.05. So it can be concluded that there is a weak correlation between the attitude and reading variables.